The role of local land-use on the urban heat island effect of Tel Aviv as assessed from satellite remote sensing. (January 2015) - Rotem-Mindali, Orit; Michael, Yaron; Helman, David; Lensky, Itamar M.
Abstract: Climate change in cities has received much focus in the past few decades. Heat stress in urban areas has an adverse effect on human health and is expected to worsen in the future due to the global warming. Vegetation has been shown to mitigate this effect, but introducing 'green' areas into the metropolitan space is a challenging task. We assessed the thermal load in terms of surface temperature in Tel Aviv, the biggest metropolitan area of Israel. The thermal effect of four different urban land uses was estimated. Specifically, we compared the cooling effect of residential areas with high vegetation cover (referred here as 'green' residential) to that of small to medium size (2–40 ha) public parks. To this end, we used satellite data of land surface temperature (LST) and the Normalized Difference Vegetation Index (NDVI), as a surrogate for vegetation cover. High-temporal data were combined with high spatial resolutions data to produce 10-year average LST and NDVI maps at high spatial resolution over Tel Aviv. As expected, industrial areas had the highest LST due to lowest ratio of vegetation to free space area (1%), while 'green' areas displayed the lowest LST. Green residential and small-medium public parks had comparable thermal loads, with green residential having slightly lower LST (by 0.5 °C). In general, small-medium public parks displayed higher LST than expected. Inefficient use of free spaces for vegetation, i.e., relatively low vegetation cover to free space ratio, was probably the main cause for this. Public parks had a higher local cooling effect, but a less continuous one on the proximate surrounding (30–90 m from the park), probably due to their relative location in the urban fabric. Our results suggest that 'greening' areas within the private urban space should be encouraged at the expense of building new small-medium parks in metropolitan areas that lack the sufficient free space for larger parks. The outcome of this study may have key implications for urban planners seeking to mitigate urban heat island effects under the limitation of existing dense urban layout. Highlights: Mitigating UHI in a dense urban fabric, could be accomplished by creating continuous green residential neighborhoods. A similarity exists, in terms of vegetation cover and temperature, between green residential sites and public parks. Vegetation was denser in private gardens probably due to better irrigation affecting plant transpiration and reducing thermal load. The location of the public parks, which is usually near roads and parking lots diminish their cooling effect. The constraint of existing dense urban layout does not dismiss alternative planning policy to public parks.